Peran Strategis Perempuan dalam Rantai Nilai Ekonomi Usaha Mikro Pengolahan Pisang di Kabupaten Seruyan - Winarti, Lili; Permadi, Rokhman (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Household-scale banana processing enterprises managed by women in Seruyan Regency hold strategic potential to increase income and empower rural women economically. This study aims to: (1) analyze income from kepok banana processing businesses, (2) measure the value added generated from processing activities, and (3) explore forms of women's empowerment within the traditional food value chain. A mixed-methods approach was employed. Quantitative data were analyzed using income formulas and the Hayami method, while qualitative data were thematically analyzed through in-depth interviews with 15 female business owners. The results show an average net income of IDR 142,351 per production cycle, with a value-added ratio of 90.83% of the output value. Women played a central role in production and business decision-making. Beyond economic contribution, this activity enhances women's control over productive assets and fosters self-confidence and social participation. These findings suggest that banana processing is a multidimensional empowerment strategy that supports local food security and rural resilience.